Marine Bioactive Compounds against Aspergillus fumigatus: Challenges and Future Prospects - Chukwuemeka Samson Ahamefule; Blessing C. Ezeuduji; James C. Ogbonna; Anene N. Moneke; Anthony C. Ike; Bin Wang; Cheng Jin; Wenxia Fang (MDPI AG, 2020)
With the mortality rate of invasive aspergillosis caused by Aspergillus fumigatus reaching almost 100% among some groups of patients, and with the rapidly increasing resistance of A. fumigatus to available antifungal drugs, new antifungal agents have never been more desirable than now. Numerous bioactive compounds were isolated and characterized from marine resources. However, only a few exhibited a potent activity against A. fumigatus when compared to the multitude that did against some other pathogens. Here, we review the marine bioactive compounds that display a bioactivity against A. fumigatus. The challenges hampering the discovery of antifungal agents from this rich habitat are also critically analyzed. Further, we propose strategies that could speed up an efficient discovery and broaden the dimensions of screening in order to obtain promising in vivo antifungal agents with new modes of action.